Alcoholism as a danger to the lives and morals of children and youths in handbooks for parents in the years 1918–1970 - Małek, Agnieszka (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The aim of this analysis is an attempt to reproduce the recommendations addressed at parents concerning the negative impact of alcohol to children. Polish guidebooks for parents from the years 1918–1970 were used as the source material for the study. Prevention of children and young people’s addiction to alcohol was the main goal of considerations undertaken in guidebooks. Pregnant women were pointed out the consequences of alcohol for the developing fetus. Moreover, authors discussed the fate of children growing up in an alcoholic family. The fact that the first contact of children with alcohol often occurred during family meetings caused the need to emphasize the influence of adults on the development of addiction in children. Research of juveniledelinquency were cited to show not only the biological side effects of alcohol but also its social consequences.
Keywords: alcoholism; health; child; upbringing; guidebooks; Second Polish Republic; Polish People’s Republic